IDDF2019-ABS-0074 Phytofabricated silver nanoparticles of phyllanthus emblica extract attenuated diethylnitrosamine induced hepatocellular carcinoma in rats via NF-κB pathway. (June 2019) - Singh, Deepika; Singh, Manvendra; Singh, Niti
Abstract : Background: Hepatic cancer is one of the deadly diseases in which multiplication of cell takes place in the liver and major cause of cancer-related mortality. The important function of NF-κB is to regulate inflammatory responses by regulating activation, survival and proliferation of the cell. Subsequently, natural based products play an important role in suppressing the proinflammatory mediators by nuclear factor-kappa B (NF-κB) pathway. Phyllanthus emblica used in the therapy of hepatocellular carcinoma. So, the current study was designed to scrutinize the protective effects of biofabricated silver nanoparticles (PEAgNPs) using Phyllanthus emblica aqueous leaves extract as NF-kB inhibitors for hepatic cancer. Methods: Fabricated silver nanoparticles using Phyllanthus Emblica aqueous extract (PEAgNPs) acts as reducing and capping agent. Biofabricated silver nanoparticles (AgNPs) were characterized by UV spectroscopy, X-ray diffraction, and Field Emission Scanning Electron Microscope with Energy Dispersive X-ray Analysis. Hepatic cancer was induced by diethylnitrosamine (a carcinogen) and further treated with PEAgNPs for 16 weeks. The anticancer effects were assessed via in vitro cytotoxic activity on HUH (hepatic cancer) cell line and by measuring a biochemical parameter in the Wistar rats. Results: In this study, PEAgNPs showed a peak at 418 nm in UV spectrophotometer with a spherical structure and gives a crystalline peak of silver in XRD pattern. Biosynthesized AgNPs significantly down-regulated the serum marker enzymes, elevated the levels of the enzymatic and non-enzymatic antioxidant profile, and diminish the levels of inflammatory markers (IL-6, TNF-α and IL-1β) via NF-κ pathway . Conclusions: Biofabricated silver nanoparticles exhibited remarkable productive impacts against hepatic cancer in rats and serve as a novel targeted therapy for hepatic cancer by regulating cytokines and NF-κB.